Value of Transverse Groove on the Earlobe and Hair Growth on the Ear to Predict the Risk for Coronary Artery Disease and Its Severity among Iranian Population, in Tehran City: - Arefi, Reza; Namazi, Mohammad Hassan; Safi, Morteza; Saadat, Habiboulah; Vakili, Hossein; Pishgahi, Mehdi; Alipoor Parsa, Saeed (Galen Medical Journal, 2020)
Background: The use of phenotypic parameters along with other noninvasive diagnostic modality can lead to early diagnosis of coronary artery disease (CAD) and prevent its life-threatening outcome. Recently, the application of head and face components for assessing the risk for CAD much attention has been paid. The present study aimed to assess the relationship between ear characteristics (transverse groove on the earlobe and hair growth on the ear) and the risk for CAD and its severity among Iranian patients. Materials and Methods: In this cross-sectional study, the study population consisted of 105 consecutive patients with suspected CAD undergoing coronary angiography. The severity of CAD was determined by the number of disease vessels as well as the presence of left main lesions assessed by coronary angiography. All patients were examined to evaluate the appearance of ear regarding the presence of transverse groove on the earlobe and hair growth on the ear. Results: Comparing cardiovascular parameters across the groups with and without transverse groove on the earlobe showed a higher rate of CAD as well as the higher number of involved coronary arteries than in the groups without transverse groove on the earlobe. Similarly, the presence of CAD and its higher severity were more revealed in patients with hair growth on the ear as compared to the group without this phenotype. According to multivariable logistic regression analysis and with the presence of baseline parameters, the presence of transverse groove on the earlobe and hair growth on the ear increased the risk for CAD by 2.4 and 4.4 fold, respectively. Conclusion: Along with classic cardiovascular risk factors, the role of growing hair on the ear and transverse groove on the ear to predict high risk for CAD should be considered. [GMJ.2020;8:e1443]